2016
DOI: 10.1016/j.orggeochem.2015.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Weathering of pyrogenic organic matter induces fungal oxidative enzyme response in single culture inoculation experiments

Abstract: The addition of pyrogenic organic matter (PyOM), the aromatic carbon-rich product of the incomplete combustion of plant biomass or fossil fuels, to soil can influence the rate of microbial metabolism of native soil carbon. The interaction of soil heterotrophs with PyOM may be governed by the surficial chemical and physical properties of PyOM that evolve with environmental exposure. We present results of a 36-day laboratory incubation investigating the interaction of a common white-rot fungus, Trametes versicol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 81 publications
(141 reference statements)
4
32
2
Order By: Relevance
“…Our results suggest that the potential positive priming of insoluble fractions of PyOM by PyOM w is greater in higher-temperature PyOM treatments (T450 and T600), where the insoluble PyOM fraction is likely greater. This is in keeping with our previous study that showed that artificially aged PyOM, which was thought to have significant amounts of leachable C, induced the enhanced oxidative enzyme response from white-rot fungi in a single culture while not being degraded itself [22]. We attributed the lack of decomposition in Reference [22] to the absence of a soil microbial consortia (present here in this study), which may benefit from the oxidative enzyme response of fungi can could lead to the further solubilization of PyOM for direct metabolism by bacterial groups [17][18][19]23].…”
Section: Pyom W Content and Estimated Pyom Recalcitrance Correlate Wisupporting
confidence: 92%
See 1 more Smart Citation
“…Our results suggest that the potential positive priming of insoluble fractions of PyOM by PyOM w is greater in higher-temperature PyOM treatments (T450 and T600), where the insoluble PyOM fraction is likely greater. This is in keeping with our previous study that showed that artificially aged PyOM, which was thought to have significant amounts of leachable C, induced the enhanced oxidative enzyme response from white-rot fungi in a single culture while not being degraded itself [22]. We attributed the lack of decomposition in Reference [22] to the absence of a soil microbial consortia (present here in this study), which may benefit from the oxidative enzyme response of fungi can could lead to the further solubilization of PyOM for direct metabolism by bacterial groups [17][18][19]23].…”
Section: Pyom W Content and Estimated Pyom Recalcitrance Correlate Wisupporting
confidence: 92%
“…It is assumed that the first-order control on PyOM reactivity in soil is determined by the pyrolysis of the initial plant material, whereby PyOM becomes progressively condensed and aromatized with increasing pyrolysis temperature [5,13,14]. While PyOM may persist for long periods of time in soil due to its acquired physicochemistry and the promotion of stabilization through soil aggregation [15,16], it is susceptible to both abiotic and biotic decomposition processes, which are influenced by the soil microbial community composition [17][18][19], soil edaphic properties [8], and exposure to chemical and photo oxidants [20][21][22][23]. Direct microbial degradation has been extensively documented.…”
Section: Introductionmentioning
confidence: 99%
“…Pyrogenic organic matter (PyOM), also called biochar or black carbon derives from incomplete combustion of organic materials including plant biomass and fossil fuels (Gibson et al, 2016). Incorporation of PyOM into soil can alter soil physicochemical properties and carbon (C) from PyOM makes up~5-45% of soil organic C (SOC) (Glaser et al, 1998;Skjemstad et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Incorporation of PyOM into soil can alter soil physicochemical properties and carbon (C) from PyOM makes up~5-45% of soil organic C (SOC) (Glaser et al, 1998;Skjemstad et al, 2002). The PyOM is highly condensed aromatic substance with high hydrophobicity and low microbial accessibility (Gray et al, 2014;Gibson et al, 2016). After adding to soils, PyOM could be eventually oxidized through abiotic and biotic processes to be hydrophilic as incorporation of oxygen-containing functional groups and accessible to soil microorganisms (Gul et al, 2015;Zimmerman, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation